(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2010)
The term ’acute abdomen’ is widely used but poorly defined. Essentially it represents a rapid onset of severe symptoms that may indicate a life threatening intra-abdominal pathology. This observational study was carried out at Combined Military Hospital (CMH) Ghatail (n=87) and CMH Momenshahi (n=63) from June 2006 to June 2007. A total of 150 patients admitted in the surgery ward clinically diagnosed as acute abdomen were studied. The goal of evaluating the patient with acute abdominal pain was to establish an early, efficient, and accurate diagnosis. When evaluating a patient with acute abdominal pain, the most important elements in making an accurate early diagnosis were the patient’s history and physical examination. Acute abdominal pain was more common in the age group 21 to 30 years (50%) with female predominance (72.67%). Some patients presented without any associated symptoms other than abdominal pain, other presented with vomiting and fever in addition to abdominal pain. Sixty two (41.33%) patients had no positive findings in laboratory investigation; radiology and ultrasonography. Most of them did not require any surgical intervention. Large fraction of cases (40%) was diagnosed as non specific abdominal pain. Maximum patients (59.33%) responded with conservative management and 40.67% patient required operative treatment. Key words: Acute abdomen, conservative management, non specific pain abdomen. DOI: 10.3329/jafmc.v5i2.4582 JAFMC Bangladesh Vol.5(2) (December) 2009, pp.36-39